Effects of Acid Modified Mineral Materials on Soil Cadmium Pollution and Plant Remediation - Zhang, Jinyang; Jin, Pengxin; Lei, Na; Li, Yin (Bangladesh Journal of Botany, 2024)
In response to the problem of soil heavy metal pollution, acid modified mineral materials were used to study the changes in adsorption performance, surface charge, and other indicators of four clay mineral materials, vermiculite, arsenic sandstone, shale, and zeolite, under acid modified conditions. The changes in soil physicochemical properties, heavy metal content, and plant growth before and after remediation were analyzed. The study showed that the introduction of acid modified adsorption materials increased the specific surface area and cation exchange capacity, enhanced adsorption performance, and provided theoretical reference for the mechanism and effect of remediation of cadmium contaminated soil. To optimize the application amount of remediation materials and develop cheap, effective, and scalable heavy metal remediation materials, it has important practical significance. Bangladesh J. Bot. 53(3): 803-809, 2024 (September) Special